Long-term follow up after endoscopic valve therapy in patients with severe emphysema - Gompelmann, Daniela; Heinhold, Tobias; Rötting, Matthias; Bischoff, Elena; Kontogianni, Konstantina; Eberhardt, Ralf; Herth, Felix (Therapeutic advances in respiratory disease, 2019)
Background and objective: Endoscopic valve therapy is a treatment modality in patients with advanced emphysema and absent interlobar collateral ventilation (CV). So far, long-term outcome following valve implantation has been insufficiently evaluated. The aim of this study was to investigate the real-world efficacy of this interventional therapy over 3?years. Methods :From 2006 to 2013, 256 patients with severe emphysema in whom absent CV was confirmed underwent valve therapy. The 3-year effectiveness was evaluated by pulmonary function testing (VC, FEV1, RV, TLC), 6-minute-walk test (6-MWT) and dyspnea questionnaire (mMRC). Long-term outcome was also assessed according to the radiological outcome following valve placement. Results :Of 256 patients treated with valves, 220, 200, 187, 100 and 66 patients completed the 3-month, 6-month, 1-year, 2-year and 3-year follow-up (FU) visit, respectively. All lung function parameters, 6-MWT and mMRC were significantly improved at 3- and 6-month FU. At 1-year FU, patients still experienced a significant improvement of all outcome parameters expect VC (L) and TLC (%). At 2?years, RV (L and %) and TLC (L and %) remained significantly improved compared to baseline. Three years after valve therapy, sustained significant improvement in mMRC was observed and the proportion of patients achieving a minimal clinically important difference from baseline in RV and 6-MWT was still 71% and 46%, respectively. Overall, patients with complete lobar atelectasis exhibited superior treatment outcome with 3-year responder rates to FEV1, RV and 6-MWT of 10%, 79% and 53%, respectively. Conclusions: Patients treated by valves experienced clinical improvement over 1?year following valve therapy. Afterwards, clinical benefit gradually declines more likely due to COPD progression.The reviews of this paper are available via the supplemental material section.
Gesehen am 05.12.2019